2010
DOI: 10.1177/1049732310372377
|View full text |Cite
|
Sign up to set email alerts
|

Facing Existential Realities: Exploring Barriers and Challenges to Spiritual Nursing Care

Abstract: Although nurses of the past and present recognize the importance of spiritual care to health and healing, in practice and education, spiritual care dwells on the periphery of the profession. The purpose of this study was to gain a better understanding of the reasons behind this contradiction. Using the phenomenological approach, open-ended interviews were conducted with 29 individuals, including oncology nurses, patients and their families, chaplains, and hospital administrators. Their accounts reveal examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 49 publications
2
58
0
4
Order By: Relevance
“…This group of nurses already had a high respect for the spirituality of their patients before the education session. This supports the literature that stated nurses respect spirituality but are unsure of how to provide spiritual nursing care (Ross, 2006, McEwen, 2004, Carr, 2010.…”
Section: Most Of the Nurses Attended Secular Universities (69%) Thissupporting
confidence: 77%
See 2 more Smart Citations
“…This group of nurses already had a high respect for the spirituality of their patients before the education session. This supports the literature that stated nurses respect spirituality but are unsure of how to provide spiritual nursing care (Ross, 2006, McEwen, 2004, Carr, 2010.…”
Section: Most Of the Nurses Attended Secular Universities (69%) Thissupporting
confidence: 77%
“…A major barrier to nurses providing spiritual care is nurses do not see themselves as spiritual caregivers (Ross, 2006& McEwen, 2004. Furthermore, Carr (2010) reported that nurses perceive that the rise of professionalism has labeled some spiritual care practices as crossing professional boundaries, and workplace stressors and decreased time to provide holistic care creates moral distress. These factors along with the fear of their own mortality prevent nurses from providing spiritual care (Carr, 2010).…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…In professional practice, there is still lack of holistic view, in other words, the need to see human beings as 'bio-psycho-social-spiritual' beings who transcend the physical aspect. (10,14) 'Readiness for enhanced coping' (39.3%) was not identified in other studies. This may occur be-cause it is associated with 'Increased readiness for spiritual well-being', although NANDA does not directly report it.…”
Section: Discussionmentioning
confidence: 83%
“…However, the defining characteristics of these diagnoses are expressed in the bond of the therapeutic treatment, and the diagnosis itself can be confirmed by the patients' self-report, with the nurses responsible only for the qualified listening. (13)(14)(15) It is noticed that little has been done in terms of spiritual needs. Therefore, there is a gap in assistance, in opposition to the theory of Wanda Horta, which points spirituality as a basic need of human beings to be observed and cared for by the nurses in their care planning.…”
Section: Discussionmentioning
confidence: 99%